Embodying critical and corporeal methodology: Digital storytelling with young women in eating disorder recovery - LaMarre A; Rice C (Massey University)
Digital storytelling is as an arts-based research method that offers researchers an opportunity to engage deeply with participants, speak back to dominant discourses, and re-imagine bodily possibilities. In this article, we describe the process of developing a research-based digital storytelling curriculum exploring eating disorder recovery. We have built this curriculum around research interviews with young women in recovery as well as research and popular literature on eating disorder recovery. Here, we highlight how the curriculum acted as a scaffolding device for the participants’ artistic creation around their lived experiences of recovery. The participants’ stories crystallize what resonated for them in the workshop process: they each have an open-ended narrative arc, emphasize the intercorporeality of recovery, and focus on recovery as process. The nuances within each story reveal unique embodied experiences that contextualize their recoveries. Using the example of eating disorder recovery, we offer an illustration of the possibilities of digital storytelling as a critical arts-based research method and what we gain from doing research differently in terms of participant-researcher relationships and the value of the arts in disrupting dominant discourses.
Keywords: 1608 Sociology